Rare extraspinal cause of acute lumbar radiculopathy. (28th October 2018) - Tieppo Francio, Vinicius; Barndt, Brandon; Schappell, Justin B; Allen, Travis; Towery, Chris; Davani, Saeid
Abstract : A 60-year-old man presented to an outpatient pain management clinic with antalgic gait and left lower extremity (LLE) radiculopathy from an unknown aetiology. A lumbar MRI revealed minimal disc protrusion at L3 and a partially visualised left-sided kidney abnormality. Abdominal and pelvic CT demonstrated severe hydronephrosis of the left kidney compressing the left psoas major. The patient was immediately referred to an outside hospital for nephrology workup, and following nephrostomy tube, his radicular pain resolved. He remained asymptomatic at 4 weeks follow-up. We found two cases of postsurgical, retroperitoneal fluid collection that caused lumbar radiculopathy, but none associated with hydronephrosis. To our knowledge, this is the first case in the literature to report hydronephrosis as the potential aetiology of lumbar radiculopathy, which highlights an important clinical reminder: to consider extraspinal aetiologies in all patients who present with lumbar radiculopathy, when clinical symptoms, examination findings and diagnostic studies present with unusual characteristics.